Answer:
a. For equation
value of x are 1 and -6.
b. For equation
value of x are 3 and -8
c. For equation
value of x are -1 and 1.
Solution:
a)Given equation is
![x+5=(6)/(x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vfn07tr4hk4fkb5jc7xwmso1jxaoj18sji.png)
On cross multiplying we get,
x(x+5)=6
![x^(2)+5 x-6=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3ddfs3zply14labwzb3n3vtz7mpwqbvki9.png)
On splitting the middle term we get,
![\begin{array}{l}{=x^(2)+6 x-x-6=0} \\ {=x(x+6)-1(x+6)=0} \\ {=(x-1)(x+6)=0}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5afi7vr866f6e6tzc2945x61l4duakakrk.png)
When x - 1 = 0 , x = 1
When x + 6 = 0 , x = -6
So two values of x which satisfies the given equation are 1 and -6.
b)Given equation is
![x=(24)/(x)-5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/eayxln5f1e7y4kdf8mfc2je4i0hjzgvnfb.png)
![\begin{array}{l}{=x * x=24-5 x} \\ {=x^(2)+5 x-24=0}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hbsf6dyfiarvpj8323ue39ur2tnwzvb6ws.png)
On splitting the middle term we get
![\begin{array}{l}{=x^(2)+8 x-3 x-24=0} \\ {=x(x+8)-3(x+8)=0} \\ {=(x-3)(x+8)=0}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dnyspqswflzd0vjdquv2w1o8q5lqi2s9cc.png)
When x - 3 = 0 , x = 3
When x + 8 = 0 , x = -8
So two values of x which satisfies the given equation are 3 and -8.
c) Given equation is
![x=(1)/(x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/knwycj1ct1uhee1jhs1apt0p8kymrd0ju4.png)
![\begin{array}{l}{=x * x=1} \\ {=x^(2)-1=0} \\ {=x^(2)-1^(2)=0}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xukeyampmqb24te13qw5wddb7jflg6auol.png)
Using algebraic identity
we get
=(x-1)(x+1)=0
When x - 1 = 0 , x =1
When x + 1 = 0 , x = -1
So two values of x which satisfies the given equation are 1 and -1.